Maternal factors associated with fetal macrosomia according to the national survey of demographics and family health 2020: Factores maternos asociados a macrosomía fetal según la encuesta nacional de demografía y salud familiar de 2020 - Ruiz Canchucaja, Angela (2022)
Introduction: Fetal macrosomia is an embarrassing condition that causes complications in short, medium and wide placenta for the fetus, both pregnant and pregnant. Objectives: To determine the maternal factors associated with fetal macrosomia following the national demographic and health survey 2020. Materials and methods: Observational, retrospective, analytical, cross-sectional study carried out in the ENDES survey in the period 2020 to 5096 women aged 12 to 49 years who they meet the established criteria. For the statistical analysis, SPSS version 25 is used, the F sample corrected for complete samples and a significance level of 0.05. Results: The prevalence of fetal macrosomia is 7.5%. Multivariate analysis found that, among personal factors, maternal edema has a significant association with fetal macrosomia (RPa 1.04, 95% IC 1.008 - 1.078). Of the pathological factors, maternal obesity has a significant association with fetal macrosomia (RPa 1.05, 95% CI 1.027 - 1.080). Of the social and demographic factors associated with fetal macrosomia, no variable describes a significant association. Conclusion: It was determined that maternal age over 34 years and maternal obesity are factors associated with a higher prevalence of fetal macrosomia.